2015
DOI: 10.1016/j.cell.2015.03.029
|View full text |Cite
|
Sign up to set email alerts
|

The Cellular Mechanisms of Neuronal Swelling Underlying Cytotoxic Edema

Abstract: Cytotoxic brain edema triggered by neuronal swelling is the chief cause of mortality following brain trauma and cerebral infarct. Using fluorescence lifetime imaging to analyze contributions of intracellular ionic changes in brain slices, we find that intense Na(+) entry triggers a secondary increase in intracellular Cl(-) that is required for neuronal swelling and death. Pharmacological and siRNA-mediated knockdown screening identified the ion exchanger SLC26A11 unexpectedly acting as a voltage-gated Cl(-) ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
219
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(243 citation statements)
references
References 65 publications
(64 reference statements)
7
219
0
2
Order By: Relevance
“…Cellular swelling occurs after cerebral trauma, stroke, spreading depression and epilepsy (Rungta et al, 2015; Stokum et al, 2016). There is a pressing need for pharmacological interventions that limit swelling and prevent the damage resulting from cells being damaged while expanding into the closed volume of the cranium.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular swelling occurs after cerebral trauma, stroke, spreading depression and epilepsy (Rungta et al, 2015; Stokum et al, 2016). There is a pressing need for pharmacological interventions that limit swelling and prevent the damage resulting from cells being damaged while expanding into the closed volume of the cranium.…”
Section: Discussionmentioning
confidence: 99%
“…1) leads to energy-dependent ion channel failure and intracellular sodium and water retention. Rungta et al established that the Na + Cl − receptor SLC26A11 is a critical modulator of intracellular transport of chloride and subsequent cerebral edema after ischemia [46]. The authors showed that blockade of this receptor attenuated cytotoxic cerebral edema [46] after HIBI.…”
Section: Secondary Injurymentioning
confidence: 99%
“…Rungta et al established that the Na + Cl − receptor SLC26A11 is a critical modulator of intracellular transport of chloride and subsequent cerebral edema after ischemia [46]. The authors showed that blockade of this receptor attenuated cytotoxic cerebral edema [46] after HIBI. The role of Na + Cl − receptor antagonism after HIBI is yet to be clarified but represents a future therapeutic target.…”
Section: Secondary Injurymentioning
confidence: 99%
“…Such reduction in size happened in the ONC/SHAM group and is a hallmark of RGC degeneration 18 . In contrast, with our repeated in vivo imaging we were able to demonstrate that the surviving neurons were slightly but significantly increased in size (17%) after ONC/rtACS compared to baseline, but this moderate swelling was clearly smaller than the characteristic swelling of an acute toxic oedema 55, 56 . Therefore we suggest that this moderate swelling is a sign of long-term survival or neuronal plasticity 51, 57 and not an indicator of future cell death.…”
Section: Discussionmentioning
confidence: 59%